Feasibility of the area reduction post-closure technique for bedside weaning of veno-arterial extracorporeal membrane oxygenation - Xu, Chen; Xu, Guo-xiong; Cao, Yi-fei; Chen, Lei; Jin, Yi-qi (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the safety and efficacy of the area reduction post-closure technique for bedside weaning of veno-arterial extracorporeal membrane oxygenation (V-A ECMO).MethodsA retrospective study was conducted from December 2022 to November 2023, analyzing data from patients who underwent V-A ECMO weaning at our center. The area reduction post-closure technique, utilizing two ProGlide devices (Abbott Vascular, Santa Clara, CA), was adopted as a standard practice. The technical success was defined as achieving complete hemostasis without a bailout open repair. The complications associated with access included hemorrhagic events, pseudoaneurysm formation, limb ischemia, distal embolization, and wound infections.ResultsA total of 18 patients were included. The median age of the cohort was 72.0 years [interquartile range (IQR), 57.5–81.5 years], with a male-to-female ratio of 2:1. The median size of arterial sheath utilized was 18.0 Fr (IQR, 17.0–20.0 Fr). The median duration of the procedure was 10.0 min (IQR, 9.0–13.0 min), and the median length of total hospital stay was 31.0 days (IQR, 25.5–39.0 days). Furthermore, the technique demonstrated a success rate of 100%. One patient (5.6%) experienced minor bleeding, which was successfully managed through compression. No additional complications associated with access were observed after the procedure.ConclusionsThe post-closure area reduction technique emerges as a viable option for bedside weaning of V-A ECMO. Nonetheless, it is essential that this technique be validated through larger comparative studies.